A Narrative Review of Biosimilars, GLP-1 Therapies, and Specialty Medication Management: An Interprofessional Perspective Including Health Assisting, Dentistry, Nursing, Health Informatics, Emergency Services, and Pharmacy - Mulfi E1, Almuharraq, Lafi; Hind Mohammed Abdulrahman Mustafa Alshanqeti; Amal Muhesan Almutairi; Hashima Makki Mohammed Jabour; Ahmad Warnas Rakha Al-Falih; Lafi Nasser Zahra Al-Anzi; Hassan Mohammad Ahmad Wadani; Salem Ibrahim Ali Al-Ghamdi; Fahad Safar Burays Al-Ghamdi; Eman Gaber Mubarki; et al. (Saudi Journal of Medicine and Public Health, 2024)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The rapid expansion of biosimilars and glucagon-like peptide-1 (GLP-1) receptor agonists has transformed chronic disease management but introduced complex challenges in access, cost, adherence, and supply chain stability. These specialty medications require coordinated interprofessional management across multiple health disciplines. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This narrative review synthesizes evidence from 2015–2024 to evaluate biosimilars and GLP-1 therapies through the lens of six health professions: health assisting, dentistry, nursing, health informatics, emergency services, and pharmacy. We focus on access barriers, economic impacts, patient counseling needs, supply chain vulnerabilities, and expanding clinical services. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A structured literature search of PubMed, Scopus, and Web of Science was conducted using keywords related to biosimilars, GLP-1 agonists, specialty pharmacy, and interprofessional care. Peer-reviewed articles, health policy reports, and grey literature from 2015–2024 were included. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Biosimilars reduce biologic costs by 15–35% but face adoption hesitancy. GLP-1 agonists demonstrate significant efficacy in diabetes and obesity but cost >1,000/month, driving insurance coverage disparities. Supply chain disruptions for GLP-1s have persisted since 2022. Interprofessional strategies—including pharmacist-led prior authorization, nurse-administered counseling, health informatics-driven shortage forecasting, emergency protocols for adverse events, dental monitoring of oral complications, and health assistant support for adherence—improve outcomes across all domains. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Integrated specialty medication management requires deliberate role expansion for all six health professions. Policy reforms, interprofessional education, and technology investments are essential to optimize access, safety, and equity.